Research on UAV Line Inspection System of Transmission Line Electrical Automation Technology - Juanjuan Wang , Yanan Wang (Forest Chemicals Review)
Electric power transmission lines have a wide coverage area, complex terrain and harsh natural environment. The line foundation, towers, ground wires, and hardware are violated by the outside world, resulting in defects and hidden dangers. This can easily lead to line failures. This seriously threatens the safety and stable operation of the power grid. In view of the low degree of automation of manual operation of unmanned aerial vehicles for transmission line inspection at present, and the difficulty of standardization and standardization of manual operation of unmanned aerial vehicles, resulting in long line inspection time or multiple crashes, the unmanned aerial vehicle proposed by China Southern Power Grid Corporation has no problem. Humans control the autonomous line inspection targets, and develop an intelligent inspection method for transmission line multi-rotor UAVs based on carrier phase differential positioning technology.